The Influence of Religiosity, Education Level and Income Level on Waqf Intention to Cash Waqf Linked Deposits at Bogor - Asmy, Sinsin; Umari, Zuul Fitriani; Zulfikri, Zulfikri (Management of Zakat and Waqf Journal (MAZAWA), 2025)
This study aims to analyze the influence of religiosity, education level, and income on the intention to donate waqf through Cash Waqf Linked Deposit (CWLD). CWLD is an Islamic waqf innovation that places waqf funds in Islamic bank deposits, where the returns are utilized for social activities such as public facilities development, education, and healthcare. This research employs a quantitative method with purposive sampling, involving 80 respondents from Institut Pertanian Bogor (IPB) who have participated in CWLD. Data was collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The findings indicate that religiosity does not significantly affect the intention to donate waqf (p = 0.726), while education level (p = 0.000) and income (p = 0.018) have significant influences. This suggests that individuals with higher education and income levels are more likely to participate in CWLD. In conclusion, increasing waqf literacy, expanding socialization, and implementing inclusive policies are necessary to enhance CWLD accessibility, allowing it to contribute more effectively to Indonesia's social and economic development.